2007
DOI: 10.1158/1078-0432.ccr-07-0121
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening and Chromosomal Abnormalities in Intestinal Metaplasia of the Urinary Bladder

Abstract: Purpose: Although intestinal metaplasia is often found in association with adenocarcinoma of the urinary bladder, it is unclear whether intestinal metaplasia of the bladder is a premalignant lesion. Telomere shortening has recently been implicated in epithelial carcinogenesis. We used quantitative fluorescent in situ hybridization (FISH) to measure telomere length and UroVysion FISH to detect cytogenetic abnormalities in urinary bladder specimens with intestinal metaplasia. Experimental Design: Paraffin-embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 34 publications
7
36
0
Order By: Relevance
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 73%
“…Primary bladder adenocarcinoma are divided into urachal and non-urachal adenocarcinoma respectively based on their location, the later being the most common. [5] Based on morphology it is classified as follows adenocarcinoma not otherwise specified, colonic type, mucinous, signet ring cell , clear cell type, hepatoid and mixed type. [6] The prognosis depends on the stage of disease, 5 year survival of 70 -100 % in patients with tumor confined to bladder, however less than 30 % present at early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the usual type of CG is considered a benign epithelium metaplasia, IM has been suggested to be a precursor in the development of adenocarcinoma [10,11]. However, other findings did not support IM's preneoplastic role [12].…”
Section: Discussionmentioning
confidence: 99%